Corporate governance and quality of financial statements: a study of listed Nigerian banks - Uwalomwa Uwuigbe; Eluyela Damilola Felix; Olubukola Ranti Uwuigbe; Obarakpo Teddy; Falola Irene (Banks and Bank Systems, 2018)
This study investigated the influence of Corporate governance on the timeliness of financial reports of listed banks in Nigeria. In order to provide answers to the research questions raised in this study, data were generated from the annual report of the listed banks on the Nigerian Stock Exchange considering the period 2008–2015. The study used Board size, Board Independence and Foreign Executives on the board as proxies for corporate governance. The data were analyzed using descriptive statistics, correlation matrix and panel data regression analysis. It was observed that board size had a non-significant negative relationship with the timeliness of financial reports. Also, the study observed that board independence also had a non-significant negative relationship with the timeliness of financial reports. Finally, it was observed that foreign executives on the board had a significant positive relationship with the timeliness of financial reports. The study thus recommends that the existing legal framework in Nigeria should be developed that clearly specifies the rights and obligations of a bank, its management and, of course, other stakeholders.